ASSOCIATION BETWEEN BENIGN PROSTATIC ENLARGEMENT, ERECTILE DYSFUNCTION AND METABOLIC SYNDROME - Griffin M, J. Mohammed Farooq; Sivasankar, Dev Krishna Bharathi (Obstetrics and Gynaecology Forum, 2024)
ABSTRACT The overwhelming evidence of a connection between lower urinary tract symptoms (LUTS) and erectile dysfunction (ED) comes from numerous major epidemiological research. Clinical data indicates that the development of ED, LUTS, and metabolic syndrome is caused by a number of shared pathophysiological pathways. The association between ED and metabolic syndrome in patients presenting with LUTS due to BPE was conducted at the Department of Urology, Saveetha Medical College. The study comprised 100 patients, whose ages ranged from 45 to 84 years old, with a mean age of 63.8 years. The physical attributes and laboratory results of the patients were tabulated. Based on the IPSS classification of patients' LUTS, 15%, 46% and 39% were found in the mild, moderate and severe LUTS patient groups. It was found that the severity of LUTS increased as people aged, but statistically insignificant(p>0.05). Regarding the severity of LUTS, there was no discernible difference in LUTS between the groups with mild/no ED and moderate/severe ED (p=0.314). 25% had diabetes mellitus, 48% had central obesity, 40% had increased triglycerides, 65% had lower HDL cholesterol, and 24% had systemic hypertension. Out of 100 patients, 36 patients satisfied three out of the five criteria and were diagnosed with metabolic syndrome. 11% had no ED, whereas 58% had mild ED, 23% had moderate ED, and 8% had severe ED. An increase in ED severity was noted with increasing age(p=0.01). There was a significant difference in the presence of metabolic syndrome between the groups with mild/no ED and moderate/severe ED (p=0.029). It was discovered that there was no correlation between the severity of LUTS and the existence of metabolic syndrome (p=0.152). Regarding the occurrence of metabolic syndrome, there is a substantial difference between the groups with mild or no ED and those with moderate or severe ED. A BPE patient was more likely to have ED than a patient without metabolic syndrome if they also had an additional diagnosis of this condition. In a patient with BPE, the existence of ED may be a predictor of metabolic syndrome.